Ion conduction in Na＋ containing ionogels based on the UiO-66 metal organic framework. (1st December 2022) - Ferbezar, Antonija; Zettl, Roman; Fitzek, Harald; Gadermaier, Bernhard; Hanzu, Ilie
Abstract: conducting materials are critical to the development of solid-state sodium batteries which may enable the use of sodium metal anodes. Ionogels are hybrid liquid–solid electrolytes that are made by embedding an ionic liquid into a suitable solid framework. In this study, ionogels based on the UiO-66 type metal organic framework (MOF) porous structure were prepared. Three isostructural MOFs were synthesized and used: (i) the UiO-66 material, (ii) an amine functionalized MOF (UiO-66- ) and iii) a hydroxyl functionalized MOF (UiO-66- ). A mixture of sodium bis(fluorosulfonyl)imide (NaFSI) and 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMIM-FSI) was embedded in the pores of the MOFs. FTIR and conductivity spectroscopy were used to asses the interaction of the mobile species with the MOF structure as well as ion transport and electric relaxation properties of the materials. We found that the conductivity of the ionogels is strongly influenced by the functionalized linker used. The UiO-66- -based ionogels present an encouraging conductivity increase trend when sodium ions are present, whereas the UiO-66- -based ionogels present the highest conductivity in the order of 0.3 mS cm −1 at 293 K, albeit this is very likely due to highly mobile protons. While further studies are needed to understand which species are dominating the ion conduction, this investigation offers an insight into the behavior of MOF-based ionogels and may guide further work in the field. Graphical abstract: Highlights: Ionogels were made by embedding ionic liquids into MOFs of the UiO-66 family. Chemical functionality of the MOF linker strongly influences ionic conductivity. Amine functionalization increases the ionic conductivity by 4 orders of magnitude. Hydroxyl functionalized MOFs reach 0.3 mS cm −1 at 293 K, protons are likely mobile.